Lydgate's Fabula duorum mercatorum and Guy of Warwyk - Lydgate, John, 1370?-1451? (Middle English texts series, 2016)
"The Fabula Duorum Mercatorum, a romance that in its Boethian sensibility and treatment of love and friendship bears comparison to Chaucer's great works Troilus and Criseyde and The Knight's Tale, is one of Lydgate's most accomplished works. In Guy of Warwick, Lydgate breaks with romance tradition, presenting from a historical point of view the heroic English knight-pilgrim and his last great battle against the dread giant Colbrond."--